SINTESIS DAN KARAKTERISASI BETON GEOPOLIMER BERBASIS ABU LAYANG SEBAGAI MEDIA TANAM - Admin APERTI (Aliansi Perguruan Tinggi Badan Usaha Milik Negara (APERTI BUMN), 2018)
In this research, geopolymer based fly ash was synthesized to be applied as planting media, especially on hydroponics system. Variables used in this study were variations of alkali NaOH and KOH with concentrations of 2M, 3M, and 4M in each alkali. In addition, variations in the ratio of solids / liquids to the geopolymer formulations of 75:25 and 70:30 were added. The Na2SiO3 was added for a perfect geopolymerization process. After geopolymer was formed, the result of material was leached with distilled water until pH becomes 6-7 making it suitable for planting media application. In each variable, the porosity (related to the ability of the material to absorb water) were determined and characterized by X-Ray Diffraction (XRD) to clarify that the phase formed indicates the geopolymerization process. Based on the research that has been done, it found that geopolymer of NaOH 4M 75:25 has highest porosity of 2.4%wt which indicate high ability to absorp water and nutrient. While optimum geopolymer conditions for planting medium which showed solution pH of 7 after immersed for four days were KOH 4M 75:25 and NaOH 4 M 70:30.